Fiscal Constitutions - Hans Gersbach (Center for Economic Studies and ifo Institute (CESifo), 1999)
In this paper we examine how individuals should be treated with respect to taxes, subsidies and agenda setting in constitutions in order to obtain efficient allocations of public goods and to limit tax distortions. We show that if public goods are socially desirable, the simple majority rule as well as taxation constrained to majority winners or a ban on subsidies are second-best constitutions. Equal treatment regarding taxes and subsidies is undesirable . Super majority rules and equal treatment of all citizens with respect to taxes and subsidies, however, is first-best if public goods are socially undesirable. The ex ante expectation of the share and welfare improvements of socially efficient public goo ds determines which constitution a society will adopt.
Keywords: 330; Incomplete social contracts; constitutions; treatment rules; majority rules